Interactive Control Systems Using the Attention-Based View: A Case Study at PT ABC - Mohamad Rifki Setyanto; Nureni Wijayati (UNIVED Press, 2026)
This study explores the implementation of interactive control systems (ICS) with an attention-based view (ABV) in managing strategic uncertainties resulting from the introduction of safeguard duties (BMTP) on imported carpet and textile floor coverings in Indonesia. With the global market dynamics and the challenges posed by regulatory changes, companies such as PT ABC have to adapt their business strategies to remain competitive. The research assesses how management focuses its attention on critical issues in this volatile environment, particularly regarding BMTP. Using a case study approach, the research analyzes how management interacts, allocates attention, and utilizes strategic information to make informed decisions. The findings emphasize the importance of interactive control systems in fostering creativity, accelerating strategic discussions, and enhancing organizational responsiveness to external uncertainties.